Pengaruh Substitusi Fly Ash pada Semen dengan Tambahan Limbah Polyehtylene Terephthalate (PET) terhadap Sifat Beton Self Compacting Concreate (SCC) - Bambang Ari Suseno; Fakih Thorik Alfiansyah (JURAL RISET RUMPUN ILMU TEKNIK, 2026)
Self-Compacting Concrete (SCC) requires a high cement content, which contributes to increased carbon emissions; therefore, this study evaluates the effect of partial cement substitution with fly ash (5%, 10%, and 15%) and the addition of Polyethylene Terephthalate (PET) waste (0.5% and 0.7%) on the mechanical properties of SCC with a target strength of f’c 30 MPa. The research employed laboratory experimental methods, including fresh concrete tests (slump flow, L-box, and V-funnel) and hardened concrete tests (compressive, tensile, and flexural strength) at 7 and 28 days. The results indicate that fly ash substitution enhances compressive strength, with the highest value of 49.59 MPa achieved at 5% fly ash at 28 days, exceeding normal concrete (34.73 MPa). The addition of PET tends to reduce compressive strength due to increased porosity; however, it significantly improves flexural strength, as the combination of 5% fly ash and 0.5% PET achieved 4.7 MPa compared to 2.9 MPa for normal concrete. Overall, the combination of fly ash and PET waste shows potential for application in structural elements requiring high flexural performance.